Ethics Philosophy of Iraqi Stage Actresses - Assist. Prof. Dr. Hayder Attallah Abd Ali (PhD) (Genius Journals, 2022)
Studies regarding the persona of the Iraqi actor haven't got the same amount of attention as has the performance, despite the importance of the actor as a human being and what is related to him, especially the ethical issues that limited the rise of many artistic talents on the stage. On that basis, the researcher stresses the need to investigate the philosophy of ethics in terms of the actresses' viewpoints. Hence, the title of the research "Ethics Philosophy of Iraqi Stage Actresses" is chosen. The present study's main aim is identifying the philosophy of Ethics according to the actresses on the Iraqi stage. The study includes four sections; the first of which identifies the problem of the study, its importance, and limitations. The second section constitutes the theoretical frame of the study which is divided into two parts concerned with ethics and the sociocultural variables of the Iraqi actress. The section ends with the most prominent indicators that resulted from the theoretical framework. The third section introduces the procedure and the adopted descriptive approach in the analysis. Furthermore, the questionnaire is adopted in analyzing the randomly selected data. The chapter ends with discussing the most important results from data analysis which are regarded as the lead to the intended conclusion of the research which reveals that Iraqi actresses believe in the pluralism of views. Finally, the study introduces recommendations and suggestions for the necessity to follow up such topic.
Keywords: Ethics; Philosophy; Actress